Nuclear security the problems and the road ahead - Shultz, George Pratt 1920-2021 (Hoover Inst. Press, 2014)
"Concern about the threat posed by nuclear weapons has preoccupied the United States and presidents of the United States since the beginning of the nuclear era. Nuclear Security draws from papers presented at the 2013 meeting of the American Nuclear Society examining worldwide efforts to control nuclear weapons and ensure the safety of the nuclear enterprise of weapons and reactors against catastrophic accidents. The distinguished contributors, all known for their long-standing interest in getting better control of the threats posed by nuclear weapons and reactors, discuss what we can learn from past successes and failures and attempt to identify the key ingredients for a road ahead that can lead us toward a world free of nuclear weapons. The authors review historical efforts to deal with the challenge of nuclear weapons, with a focus on the momentous arms control negotiations between U.S. president Ronald Reagan and Mikhail Gorbachev. They offer specific recommendations for reducing risks that should be adopted by the nuclear enterprise, both military and civilian, in the United States and abroad. Since the risks posed by the nuclear enterprise are so high, they conclude, no reasonable effort should be spared to ensure safety and security."--Back cover
Includes index
Reducing nuclear threat: lessons from experience -- Challenges to maintaining trust in the safety and security of the nuclear enterprise -- Nuclear risk: the race between cooperation and catastrophe -- The Gipper's guide to negotiating -- What a final Iran deal must do -- Is it illogical to work toward a world without nuclear weapons? -- Final thoughts
Keywords: Nuclear arms control / Congresses; Nuclear reactors / Safety measures / Congresses; Nuclear weapons / Security measures / Congresses; Kernreaktorsicherheit; Kernwaffe; Atomare Abrüstung; Aufsatzsammlung; Konferenzschrift